Agreement between Subjective and Objective Parameters Using Meibography for Assessment of Dry Eye Syndrome - Taimoor, Ijlal; Naqvi, Syed Abid Hassan; Khan, Taimoor Ashraf; Naeem, Saquib; Yousaf, Waseem; Ghani, Muhammad Usman (Pakistan Armed Forces Medical Journal, 2023)
Objective: To determine the agreement between subjective and objective parameters using meibography.Study Design: Cross-sectional observational study.Place and Duration of Study: Armed Forces Institute of Ophthalmology (AFIO), Rawalpindi Pakistan from August 2021 till February 2022.Methodology: 100 patients were included in the study. Non-contact infra-red meibography was performed on each patient. Subjective assessment was done using the four-grade and five-grade scales while objective assessment was done by applying computerized grading.Results: A total of one hundred (n=100) patients participated in the study. Out of total, 60% patients were male and 40% were females, with a mean age 42.25±14.9 years. There was statistically significant difference was seen Session I OII vs Session II OII as p-value